The development of professional self-organization among students //El desarrollo de la autoorganización profesional entre los estudiantes - Kirillova, Inna K.; Khusainova, Evgeniia N.; Koikova, Elzara I.; Khlyzova, Irina V.; Artamonova, Ekaterina I. (Revista de la Universidad del Zulia, 2020)
Abstract The growing volumes of information and rapidly changing requirements of the professional training of students in higher education institutions make it necessary for students to seek internal reserves to master professional skills. In modern conditions, the process of professional self-organization of students is being updated. This is reflected in the requirements of the new Russian federal state educational standards of higher education in the form of key general competencies. One of them is "the ability to manage your time, build and implement the path of self-development based on the principles of education throughout life." The purpose of the article is to review the experience of developing professional self-organization among students. Professional self-organization can be understood as the process of mobilizing the capacities of the individual to achieve goals. Professional self-organization is a constantly evolving process of internal rationalization of educational activities. The crucial thing in the learning process must belong to the control of the student, since the learning activity is characterized by the active position of the student. The article presents the experience of developing the self-organization competence based on the example of the study of the cycle of general humanistic disciplines. Both individual and group forms of work are used in the training of students, electronic means are involved. To develop independence, students, with the advisory support of a teacher, complete projects, cases, tests, final assignments and other tasks. The training of the competence under consideration allows the future specialist to successfully analyze the task, contributes to rational planning, proper evaluation, timely adjustment and improvement of the process of educational activity and its management. Resumen Los crecientes volúmenes de información y los requisitos rápidamente cambiantes de la formación profesional de los estudiantes de las instituciones de educación superior hacen necesario que los estudiantes busquen reservas internas para dominar las competencias profesionales. En las condiciones modernas, el proceso de autoorganización profesional de los estudiantes se está actualizando. Esto se refleja en los requisitos de los nuevos estándares educativos estatales federales rusos de educación superior en forma de competencias generales claves. Una de ellas es “la capacidad de administrar tu tiempo, construir e implementar el camino del autodesarrollo basado en los principios de la educación a lo largo de la vida”. El propósito del artículo es revisar la experiencia de desarrollar la autoorganización profesional entre los estudiantes. La autoorganización profesional puede entenderse como el proceso de movilizar las capacidades del individuo para lograr metas. La autoorganización profesional es un proceso en constante evolución de racionalización interna de las actividades educativas. Lo crucial en el proceso de aprendizaje debe pertenecer al control del alumno, ya que la actividad de aprendizaje se caracteriza por la posición activa del alumno. El artículo presenta la experiencia de desarrollar la competencia de autoorganización a partir del ejemplo del estudio del ciclo de disciplinas humanísticas generales. En la formación de los estudiantes se utilizan formas de trabajo tanto individuales como grupales, se involucran medios electrónicos. Para desarrollar la independencia, los estudiantes, con el apoyo asesor de un docente, realizan proyectos, casos, pruebas, trabajos finales y otras tareas. La formación de la competencia en consideración permite al futuro especialista analizar con éxito la tarea, contribuye a la planificación racional, la evaluación adecuada, el ajuste oportuno y la mejora del proceso de la actividad educativa y su gestión.